2015
DOI: 10.1051/ocl/2014056
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and ocular pathologies: focus on the role of cholesterol-24S-hydroxylase in cholesterol homeostasis

Abstract: -The retina is responsible for coding the light stimulus into a nervous signal that is transferred to the brain via the optic nerve. The retina is formed by the association of the neurosensory retina and the retinal pigment epithelium that is supported by Bruch's membrane. Both the physical and metabolic associations between these partners are crucial for the functioning of the retina, by means of nutrient intake and removal of the cell and metabolic debris from the retina. Dysequilibrium are involved in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 72 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…In accordance with a previous study [ 16 ], we found here that, in hypercholesterolemic rabbits, RPE cells showed intracellular droplets of lipids. These lipid accumulations may occur because RPE expresses a variety of lipoprotein-specific receptors (LDLR, SR-BI, SR-BII) and scavenger receptors (CD36) that enable the recognition of circulating lipoproteins by RPE and delivery to the retina [ 1 , 10 ]. The accumulation of lipids between the inner collagenous layer and the basal lamina of the BM (as seen in many older human eyes) participates in creating a physical barrier, called the lipid wall, which may limit the exchanges between the choriocapillaris and the RPE [ 10 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In accordance with a previous study [ 16 ], we found here that, in hypercholesterolemic rabbits, RPE cells showed intracellular droplets of lipids. These lipid accumulations may occur because RPE expresses a variety of lipoprotein-specific receptors (LDLR, SR-BI, SR-BII) and scavenger receptors (CD36) that enable the recognition of circulating lipoproteins by RPE and delivery to the retina [ 1 , 10 ]. The accumulation of lipids between the inner collagenous layer and the basal lamina of the BM (as seen in many older human eyes) participates in creating a physical barrier, called the lipid wall, which may limit the exchanges between the choriocapillaris and the RPE [ 10 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major consequence of the astroglial decrease (observed as a reduction of AANFB-RA and PVA-RA) in G1 could be related to the fact that these cells are an active partner of neurons by maintaining cholesterol synthesis and removal [ 1 ]. In the retina, Müller cells and astrocytes participate in the metabolism (supplying heterogeneous lipoprotein particles and ApoE) and transport of cholesterol, an essential source of lipids for the maintenance of the neuronal cell membranes [ 17 , 66 , 69 , 97 ], making neurons susceptible to alteration in long-term hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations